Phleum pratense pollen-derived di-galactosyldiacylglycerols promote pro-allergic responses in mice - González Roldán, Nestor; Lunding, Lars P.; Fujimoto, Yukari; Düpow, Sylvia; Schwudke, Dominik; Wegmann, Michael; Duda, Katarzyna A. (Frontiers in Immunology, 2025)
IntroductionGrass pollen triggers nearly 30% of bronchial allergic asthma cases. While most Q8 research focuses on pollen allergens, pollen lipids may also influence allergic reactions. Previous studies demonstrated that Timothy grass (TG, Phleum pratense) lipids, such as phytoprostanes, can activate immune cells, promoting pro-allergic responses. However, the role of water-insoluble pollen glycolipids in allergic airway inflammation remains unclear. Thus, this study aimed to isolate and characterize glycolipids from TG pollen and evaluate their bioactivity in allergic airway inflammation.MethodsLipids were extracted from the water-insoluble pollen fraction, separated by silica gel, and fractionated by HPLC. GC-MS, HR ESI-MS, and NMR confirmed the presence of di-galactosyldiacylglycerol (DGDG). The biological activity of fractions containing DGDG (DGDG-3 and DGDG-4) and synthetic DGDG variants was tested in vitro in murine and human cell systems and in vivo in mice.ResultsFraction 4 induced strong proliferation of murine NKT cells and upregulated CD69 expression in human NKT cells. Synthetic DGDG variants (DGDG-1, DGDG-2, and DGDG-3) with defined acylation profiles stimulated robust NKT-cell proliferation, with DGDG-2 and DGDG-3 increasing IL-13 production, one of the key Th2 cytokines. In vivo, only these variants caused lung inflammation marked by eosinophil infiltration but did not increase airway resistance.DiscussionThis study reveals for the first time the structure-dependent role of DGDG of TG pollen grains in immune cell recognition in the context of allergic inflammation. Our data may pave the way for therapies targeting lipid components in combination with protein allergens.